ANALISIS PENGARUH UKURAN PERUSAHAAN, FINANCIAL DISTRESS DAN OPINI AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2020 - Anggi Septa Risanty; Alfurkaniati; Burhanuddin (Journal Of Islamic Finance And Accounting Research, 2023)
This study aims to analyze the effect of Company Size, Financial Distress, and Audit Opinion on the Timeliness of Financial Reporting. The population used in this study was a Consumer Goods Industry company listed on the Indonesia Stock Exchange for the period 2018 to 2020 which amounted to 64 companies. Based on the sampling method using the Purposive Sampling method, a sample of 47 companies was obtained for 3 (three) years of observation from 2018 to 2020 with 141 observations (observations). The data analysis techniques used in this study are descriptive statistical analysis, logistic regression analysis and hypothesis testing using the SPSS 25 program. The results of this study show that Company Size and Financial Distress do not have a significant effect on the timeliness of financial reporting, while Audit Opinion has a significant effect on the Timeliness of Financial Reporting and the variables of Company Size, Financial Distress and Udit Opinion have a simultaneous effect on the timeliness of financial reporting.